Intelligent negotiation mechanism for supporting the interoperability within the sensing enterprise - Stanescu, Aurelian Mihai (2020)
The authors wish to acknowledge the support of the European Commission through the funding of the UNITE, MSEE and IMAGINE FP7 projects, and the European Space Agency - Concurrent Design Facility (ESA-CDF) for their support in the development of the business case presented in this paper.